Helminths of veterinary and zoonotic importance in Nigerian ruminants: a 46-year meta-analysis (1970-2016) of their prevalence and distribution - Solomon Ngutor Karshima; Beatty-Viv Maikai; Jacob Kwada Paghi Kwaga (BMC, 2018)
Abstract Background The livestock industry plays a vital role in the economy of Nigeria. It serves as a major source of income and livelihood for majority of Nigerians who are rural settlers and contributes about 5.2% to the National Gross Domestic Product (GDP). Helminths however, cause economic losses due to reductions in milk production, weight gain, fertility and carcass quality. Zoonotic helminths of livestock origin cause health problems in humans. Methods Using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines, the prevalence and distribution of helminths of veterinary and zoonotic importance in Nigerian ruminants were determined in a meta-analysis of data published between 1970 and 2016. Data were stratified based on regions, hosts, study periods, sample sizes and study types while helminths were phylogenetically grouped into cestodes, nematodes and trematodes. Results Data from 44 studies reported across 19 Nigerian states revealed an overall pooled prevalence estimate (PPE) of 7.48% (95% CI: 7.38-7.57) for helminths of veterinary and zoonotic importance from a total of 320 208 ruminants. We observed a significant variation (P < 0.001) between the PPEs range of 1.90% (95% CI: 1.78-2.02) and 60.98% (95% CI: 58.37-63.55) reported across different strata. High heterogeneity (99.78, 95% CI: 7.38-7.57) was observed. Strongyloides papillosus was the most prevalent (Prev: 32.02%, 95% CI: 31.01-33.11), while, Fasciola gigantica had the widest geographical distribution. Conclusions Helminths of veterinary and zoonotic importance are prevalent in ruminants and well distributed across Nigeria. Our findings show that helminths of ruminants may also be possible causes of morbidity in humans and economic losses in the livestock industry in Nigeria. High heterogeneity was observed within studies and the different strata. Good agricultural practices on farms, standard veterinary meat inspection and adequate hygiene and sanitation in abattoirs, farms and livestock markets need to be implemented in Nigeria in order to reduce the economic, public health and veterinary threats due to these helminths.